Horizontal unidirectional airflow for reducing cross-infection of COVID-19: A narrative review - Hunny Sharma; Manisha Ruikar (Wolters Kluwer Medknow Publications, 2022)
Recent decades have witnessed the emergence of many airborne diseases such as severe acute respiratory syndrome, Middle East respiratory syndrome, and COVID-19, which have highlighted the importance of effective ventilation in residential, work, or hospital premises. Ventilation which plays an essential role in reducing or diluting the airborne contaminants. However, it is not always easy to achieve by natural ventilation as it depends on many other factors such as temperature and climatic conditions. (wind velocity, wind direction, and housing pattern/design). Horizontal unidirectional airflow (HUAF) is one such method that can be achieved at low cost and can reduce cross-infection of COVID-19 to much extent. Hence, this narrative review aims to bring some insight into what is HUAF, how it can be achieved, and what are its possible implications in preventing COVID-19 transmission.